Identification and characterization of a female gametophyte defect in sdk1-7 +/- abi3-6 +/- heterozygotes of Arabidopsis thaliana. (2nd August 2020) - Sankaranarayanan, Subramanian; Jamshed, Muhammad; Delmas, Frédéric; Yeung, Edward C.; Samuel, Marcus A.
ABSTRACT: Successful reproduction in angiosperms is dependent on the highly synchronous development of their male and female gametophytes and the ensuing fusion of the gametes from these reproductive tissue types. When crossing a T-DNA insertion line sdk1-7-/- (Salk_024564), one of the S-domain receptor kinases involved in ABA responses with a fast neutron deletion line abi3-6-/-, the F1 heterozygotes ( sdk1-7+/-abi3-6 +/-) displayed 50% ovule abortion suggesting a likely gametophytic defects. We identified and characterized an early stage female gametophyte developmental defect in the heterozygous mutant ovules. Recombination frequency analysis of the F2 progenies from selfed heterozygotes revealed a possible pseudo-linkage of sdk1-7 and abi3-6 suggesting a reciprocal translocation event in the heterozygote. Our study emphasizes the importance of robust analysis to distinguish gametophytic defect phenotypes caused by genetic interactions and that resulting from possible chromosomal translocation events.